Faktor-faktor yang mempengaruhi kepuasan pelanggan di kaunter perkhidmatan pelanggan sektor kesihatan swasta :|bkajian kes di Timberland Medical Centre - Sharifah Nor Azairina, Wan Habib Ismail. (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study aims to identify the factors that influence customers’ satisfaction at customer’s service counter,Timberland Medical Centre, Kuching. Specifically, factors identified in this study are tangible, reliability, responsiveness, courtesy and competence which adapted from SERVQUAL Model by Parasuraman, Zeithaml and Berry (1988). This study also aimed to find out the level of customer’s satisfaction. A total of 114 respondents were selected based on convenient sampling and questionnaires were used as the instrument item.Data analyzed by using Statistical Package for Social Science (SPSS) Version 12.0. Descriptive Statistics is used to analyze the demographic backgroundand the level of customer’s satisfaction, meanwhile Inferential Statistics using Pearson Correlation Test to find out the relationship between independent variables which are tangible, reliability, responsiveness, courtesy and competence and dependent variables which is customer’s satisfaction and Regression Linear is used for analyzing the dominant factor that affecting customer’s satisfaction. Results from Pearson Correlation Test shows that there exists moderate relationship between customer’s satisfaction with tangible(r=0.570, p<0.01), reliability(r=0.559, p<0.01) , responsiveness(r=0.709, p<0.01), courtesy (r=0.643, p<0.01) and competence (r=0.642, p<0.01). Findings also shows that the dominant factor that affecting customer’ s satisfaction is competence. Results for measurement of customer’s satisfaction is on average level. This study is important as an early steps in giving a picture about factors that influence customer’s satisfaction so that further steps can be taken to increase the level of customer’s satisfaction.